Prenatal iodine supplementation and early childhood neurodevelopment: the PoppiE trial – study protocol for a multicentre randomised controlled trial - Lex W Doyle; Thomas Sullivan; Jeanie Cheong; Simon Wood; Tim Green; Maria Makrides; Karen P Best; Jacqueline F Gould; A J McPhee; Shao J Zhou; Rosalie Grivell; E Knight; et al. (BMJ Open, 2023)
Introduction Observational studies suggest both low and high iodine intakes in pregnancy are associated with poorer neurodevelopmental outcomes in children. This raises concern that current universal iodine supplement recommendations for pregnant women in populations considered to be iodine sufficient may negatively impact child neurodevelopment. We aim to determine the effect of reducing iodine intake from supplements for women who have adequate iodine intake from food on the cognitive development of children at 24 months of age.Methods and analysis A multicentre, randomised, controlled, clinician, researcher and participant blinded trial with two parallel groups. Using a hybrid decentralised clinical trial model, 754 women (377 per group) less than 13 weeks’ gestation with an iodine intake of ≥165 µg/day from food will be randomised to receive either a low iodine (20 µg/day) multivitamin and mineral supplement or an identical supplement containing 200) µg/day (amount commonly used in prenatal supplements in Australia), from enrolment until delivery. The primary outcome is the developmental quotient of infants at 24 months of age assessed with the Cognitive Scale of the Bayley Scales of Infant Development, fourth edition. Secondary outcomes include infant language and motor development; behavioural and emotional development; maternal and infant clinical outcomes and health service utilisation of children. Cognitive scores will be compared between groups using linear regression, with adjustment for location of enrolment and the treatment effect described as a mean difference with 95% CI.Ethics and dissemination Ethical approval has been granted from the Women’s and Children’s Health Network Research Ethics Committee (HREC/17/WCHN/187). The results of this trial will be presented at scientific conferences and published in peer-reviewed journals.Trial registration number NCT04586348.